Adenomyosis: Diagnosis and Treatment - Muhammad Faeyza Arifin Putra; Meilisva Audila Anggraini (Jurnal Biologi Tropis, 2022)
Adenomyosis is a benign invasion of endometrial tissue into the myometrium and it is one of the cause of abnormal uterus bleeding (AUB) in women. Adenomyosis is not widely discussed because the incidence and prevalence are not well known due to the certainty of diagnosis depending on histological examination which requires prior hysterectomy. This literature review aims to improve further understanding of adenomyosis by discussing two focus studies, which is to discover other diagnostic methods, and to be aware of the different ways to treat adenomyosis with different published literature in various database as the references.  Advances in imaging technology allows more non-invasive procedure such as transvaginal ultrasound (TVUS) and magnetic resonance imaging (MRI) to diagnose adenomyosis without comprimising the patient fertility. The treatment of adenomyosis are divided into two parts, medicamentosa and operative therapy. Although there is different ways to diagnose and treat adenomyosis in this era, histological examination and hysterectomy is still the gold standart and definitive therapy to diagnose and treat adenomyosis, respectively.